2014
DOI: 10.1111/1753-6405.12232
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of habit‐based informational interventions: a randomised controlled trial of fruit and vegetable consumption

Abstract: Objective: To assess the effectiveness of a habit-based intervention delivered by e-mail or sms in improving fruit and vegetable consumption among young adults.Methods: An eight-week randomised controlled trial compared the effectiveness of three different types of message content (habit-based messages; food-group messages; general healthy eating messages) and two delivery methods (e-mail versus sms) on habit strength and consumption of fruits and vegetables in 71 undergraduate participants.Results: A signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 32 publications
(41 reference statements)
3
33
0
Order By: Relevance
“…Interestingly, this was not the case as intention and habit strength did not significantly interact to predict parents' general healthy feeding indicating that for parents to be able to provide healthy food choices to their children involves both rational and automatic processes. This is in contrast to other eating behaviours whereby stronger habit strength reduces the importance of intention (De Bruijn, 2010), but is comparable to an Australian study on fruit and vegetable consumption (Rompotis, Grove, & Byrne, 2014). This could be because parents' healthy feeding practices are for their children whereas most previous studies have looked at personal eating behaviours.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, this was not the case as intention and habit strength did not significantly interact to predict parents' general healthy feeding indicating that for parents to be able to provide healthy food choices to their children involves both rational and automatic processes. This is in contrast to other eating behaviours whereby stronger habit strength reduces the importance of intention (De Bruijn, 2010), but is comparable to an Australian study on fruit and vegetable consumption (Rompotis, Grove, & Byrne, 2014). This could be because parents' healthy feeding practices are for their children whereas most previous studies have looked at personal eating behaviours.…”
Section: Discussionsupporting
confidence: 64%
“…Only 3 of the 14 studies had recruited >500 participants at baseline [ 62 - 64 ], and 1 study had a sample size of <100 [ 64 ]. More than half of the interventions were conducted in the United States [ 62 , 64 , 67 , 69 , 71 , 73 , 75 ], 4 in Australia [ 65 , 65 , 67 , 72 ], 1 in New Zealand [ 74 ], and 1 in Malaysia [ 70 ]. The target audience was college or university students for the majority of the studies [ 62 , 63 , 67 - 75 ], and 3 studies reported their target audience to be young adults [ 64 - 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…All but 2 studies recruited through the university or college setting [ 64 , 66 ]. Participants were recruited through undergraduate psychology courses in 2 studies [ 67 , 68 ], from random nonnutrition classes in 2 studies [ 69 , 70 ], and through advertisements and flyers posted on university grounds in 4 studies [ 62 , 63 , 65 , 71 , 72 ]. In 1 study a recruitment table was set up on campus [ 73 ], and another study invited patients attending the student university health service [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study design did not test the efficacy of the individual components, but the engagement data suggested that the coaching calls and text messages were useful to participants, with 100% and 90.9% reporting having used these components, respectively. A text message intervention in normal-weight young adults showed messages based on a habit framework can improve fruit consumption, and simply reminding young adults to be conscious of their food choices may be sufficient to improve their overall vegetable consumption [ 44 ]. Costs of delivering a mobile program could be reduced without coaching calls, but our previous pilot intervention did not detect effectiveness in dietary change with text messages alone, without coaching calls.…”
Section: Discussionmentioning
confidence: 99%